Nádorové multiplicity u ceské populace - Geryk, Edvard; Dítĕ, Petr; Kozel, Jirí; Kubícek, Petr; Konecný, Milan; Stampach, Radim; Pesek, Milos (Casopis lekaru ceskych, 2010)
During 1976-2005 the Czech Cancer Registry registered 1.486,984 neoplasms of categories ICD-10: C00-D48, of which were notified 290,312 (19.5%) multiple cases. There were 65,292 primary diseases in men and 59,970 in women, 89,796 subsequent neoplasms in men and 75,254 in women. The duplicities were higher in men and multiplicities higher in women. The multiple cases there were 19.5% of total new diagnosed neoplasms in men and 18.5% in women, without the skin cancers there were 13.7% in men and 13.6% in women. The most frequent were primary cancers of skin 46%, digestive tract 13.5%, urinary tract 9.6%, genital organs 8.1%, respiratory and intrathoracic organs 7.8% in men and cancers of skin 39.4%, breast 17.3%, genital organs 14.6%, and digestive tract 9.8% in women. The highest percentage of multiplicities in new diagnosed cases were cancers of skin 56.4%, melanoma 22.7%, urinary tract 19.9%, oral cavity 17.8%, genital organs 16.4%, endocrine glands 15.8% and haemopoietic tissues 13.9% in men, the cancers of skin 43.6%, oral cavity 19.8%, melanoma 18.6%, breast 17.7%, urinary tract 17.7%, genital organs 13.5% and endocrine glands 13% in women. The most multiplicities were registered in region Northern Moravia 38,547 (13.3%), Southern Moravia 34,219 (11.8%) and in Prague 34,218 (11.8%). From 125,262 patients, 18,887 (15.1%) men and 22,274 (17.8%) women survived, number of deceased persons was 46,405 (37%) men and 37,696 (30.1%) women. In the view of multiple cancers the broad education of lifestyle appears not to be sufficient for both the healthy population and for patients with 595 thousand cancers, expected in 2010.
Keywords: mnohočetné primární nádory; Česká republika; Neoplasms, Multiple Primary; lidé; Female; mužské pohlaví; Male; Czech Republic; ženské pohlaví; Humans